HIV a Bayesian structural equation modeling approach. - Palatino, Maylin C. (2012)
The paper aimed to compare the parameter estimates of Bayesian structural equation modeling (SEM) analysis using non-informative and informative prior distributions; to determine if the seafarers' HIV/AIDS-related knowledge and attitude were predictors of having risky sexual behavior during deployment; to determine if the seafarers' age was a predictor of HIV/AIDS-related knowledge and behavior; and if marital status was a predictor of the seafarers' risky sexual behavior during deployment. Four hundred-eighty respondents from Bohol and Cavite of Saniel et al (2010) were included in the study. Bayesian SEM analysis using non-informative and informative prior distributions were performed on the complete data set. Bayesian SEM using non-informative priors was performed on the Bohol seafarers' data set. The resulting posterior distributions were used as the prior distributions on the Bayesian SEM analysis that was done on the complete data set. The parameter estimates of Bayesian SEM using informative prior distributions were chosen over the parameter estimates of Bayesian SEM analysis using non-informative prior distributions. Single male seafarers were found to be more at risk of having risky sexual behaviors during deployment. Moreover, the seafarers' HIV/AIDS-related attitude was also found to be a predictor of their having risky sexual behavior during deployment. HIV/AIDS intervention programs, aside from increasing the HIV/AIDS knowledge of seafarers, should also seek to improve their attitude and appreciation on the different HIV infection prevention strategies. These intervention programs should also target single seafarers.